THE MESSAGE OF PREACHING FROM FORMER TERRORISTS ON THEIR FACEBOOK ACCOUNTS - Ahmad Zamzamy; Marijan, Kacung; Ida, Rachmah (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2025)
There has been no specific study on the preaching messages from former terrorists. This paper aims to describe the preaching messages in the Facebook accounts of former terrorists. This research method uses qualitative content analysis on text data from Facebook. The data were collected through observation and documentation of status message uploads on two Facebook accounts belonging to former terrorists and supported by related literature studies. The two Facebook accounts belonging to former terrorists generally contain preaching messages with general themes, deradicalization, and counter-radicalization. This paper shows that the preaching messages delivered by former terrorists have distinctive material that is different from other preachers. The delivery of preaching messages by former terrorists through social media platforms can have a positive impact on countering terrorism and promoting peaceful Islam.